Clarification of ambiguous problems effects on problem-solving ability and attitude towards mathematics - Sibbaluca, Luzviminda Mangino (2008)
This study tested the effectiveness of using ambiguous problems and the clarification of this kind of problems in improving the problem-solving ability and attitude of students towards mathematics. The study utilized a quasi-experimental design. Two heterogeneous sections of first year students from a public high school were randomly assigned to the experimental and the control group respectively. The experimental group was then exposed to clarification of ambiguous problems while the control group underwent the traditional method of teaching. Based on the qualitative and quantitative analyses of data, it can be concluded that the use of activities involving clarification of ambiguous problems as part of a mathematics lesson can be effective in teaching thinking skills that can be useful in improving students' problem solving ability and attitude towards mathematics.
Thesis (M.A. Mathematics Education)--University of the Philippines, Diliman.
Keywords: Mathematics -- Study and teaching (Secondary) -- Philippines; High school students -- Philippines -- Attitudes; Problem solving; Mathematical ability -- Testing